Uang Kebon : Mata Uang Lokal Perkebunan di Tanah Deli - Churmatin Nasoichah (Balai Arkeologi Sumatera Utara, 2010)
Abstract“uang kebon” (money which is used in “plantation”) is a special type of currency issued and used in Deli area of plantation, east of Sumatera. As a medium of exchange,money used by contract workers for the sale and purchase transaction where the money they normally receive as wages in the early and mid of the month. “uang kebon” or token money is often referred to using the unit of dollars and cents with the variaty of shapes and sizes according to the taste of plantation owners. “Uang kebon” is one of tools to bind the contract workers so they cannot escape from the plantation area.